Detail Engineering Design (DED) pada Struktur New Siloam Hospital Surabaya - Mochamad Hafidh Masruri; Mohamad Iqbal Fanany; Muchammad Fachru Rizal; Denni Pramudia Pamungkas; Dika Ayu Safitri (International Forum of Researchers and Lecturers, 2024)
The construction of health facilities is part of national development. Therefore, many health facility development projects, such as hospitals, continue to be carried out in various regions. One of them is the construction of the New Siloam Hospital in Surabaya. This article aims to understand the concept of detail engineering design on the building structure of New Siloam Hospital. Field surveys and data collection are the methods used to obtain information related to hospital construction projects. There are several differences between field data and work drawing data that has been created. Some of these differences include details on the reinforcement and casting volume. Therefore, it is necessary to carry out further evaluation of field data with work drawing data so that the project can proceed according to initial planning.